2010
DOI: 10.1186/1742-4682-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical framework for human SLE Nephritis: disease dynamics and urine biomarkers

Abstract: BackgroundAlthough the prognosis for Lupus Nephritis (LN) has dramatically improved with aggressive immunosuppressive therapies, these drugs carry significant side effects. To improve the effectiveness of these drugs, biomarkers of renal flare cycle could be used to detect the onset, severity, and responsiveness of kidney relapses, and to modify therapy accordingly. However, LN is a complex disease and individual biomarkers have so far not been sufficient to accurately describe disease activity. It has been po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…In one approach [96], a dynamical model was used to explain the cyclic fluctuations observed in circulating T cells in NOD mice, an animal model of T1D; the authors suggested that this may arise from a positive relation between the rate of T cell activation and the level of self-antigen on the one hand, and a negative relation between this level and the rate of immune cells differentiation on the other. In another study [97], urine biomarkers were incorporated into a mechanistic model of lupus nephritis to explain and predict the occurrence of flares in this disease.…”
Section: Hypothesis-based Models Of Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In one approach [96], a dynamical model was used to explain the cyclic fluctuations observed in circulating T cells in NOD mice, an animal model of T1D; the authors suggested that this may arise from a positive relation between the rate of T cell activation and the level of self-antigen on the one hand, and a negative relation between this level and the rate of immune cells differentiation on the other. In another study [97], urine biomarkers were incorporated into a mechanistic model of lupus nephritis to explain and predict the occurrence of flares in this disease.…”
Section: Hypothesis-based Models Of Autoimmunitymentioning
confidence: 99%
“…This approach, which was recently demonstrated in models of SLE [97], acute HCV infections in chimpanzees [112] and influenza A virus infection [113], may be particularly reasonable in diseases featuring periodic exacerbations (flares), as changes in parameter values may correspond to and point to unknown disease processes contributing to disease exacerbation. This can be done systematically by searching for the most plausible (e.g.…”
Section: How Can We Combine Hypothesis-based and Data-driven Modelmentioning
confidence: 99%
“…This distinguishes our work from models in the literature which focus on the chronic stage of SLE and assume an established autoimmune response (Budu-Grajdeanu et al. 2010 ; Gao et al. 2022 ), study organ damage in the case of Lupus nephritis (Hao et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example is the urinary biomarker, which samples are easy to collect and thought to be more accurate in distinguishing kidney disease from other organs. 5 , 6 Neutrophil gelatinase-associated lipocalin (NGAL) is a protein with a molecular weight of 25 kDa and a member of the lipocalin family. It is mainly synthesized by epithelial cells of proximal tubules, the loop of Henle, and collecting ducts of the kidney.…”
Section: Introductionmentioning
confidence: 99%